Standardized management systems in the light of employee participation in OSH – research results - Niziołek, Konrad; Boczkowska, Katarzyna (Wybrane aspekty zarządzania procesami, projektami i ryzykiem w przedsiębiorstwach, 2020)
The aim of this article is the exemplification of framework of employee participation in health and safety in the context of standardized management systems, particularly health and safety management systems. Obtained results of research carried out by the PAPI method among representatives from 195 organizations allowed to build a construct using confirmatory factor analysis. Using the developed construct, the impact of implementing standardized management systems on the level of employee participation in the area of OSH was examined. Studies have shown that the level of employee participation in OSH is determined by the fact of having any management system, although in the case of implemented OSH management systems this level is significantly higher.